ChemInform Abstract: Elusive Reaction Intermediates in Solution Explored by ESI‐MS: Reverse Periscope for Mechanistic Investigations. Issue 14 (March 2016) - Iacobucci, Claudio; Reale, Samantha; De Angelis, Francesco
Abstract: Review: [63 refs.